The Inhibition of Monoamine Oxidase by Esomeprazole - Petzer, A.; Pienaar, A.; Petzer, J. P. (Drug Research, 2013)
Virtual screening of a library of drugs has suggested that esomeprazole, the S-enantiomer of omeprazole, may possess binding affinities for the active sites of the monoamine oxidase (MAO) A and B enzymes. Based on this finding, the current study examines the MAO inhibitory properties of esomeprazole. Using recombinant human MAO-A and MAO-B, IC50 values for the inhibition of these enzymes by esomeprazole were experimentally determined. To examine the reversibility of MAO inhibition by esomeprazole, the recoveries of the enzymatic activities after dilution of the enzyme-inhibitor complexes were evaluated. In addition, reversibility of inhibition was also examined by measuring the recoveries of enzyme activities after dialysis of enzyme-inhibitor mixtures. Lineweaver-Burk plots were constructed to evaluate the mode of MAO inhibition and to measure Ki values. The results document that esomeprazole inhibits both MAO-A and MAO-B with IC50 values of 23 µM and 48 µM, respectively. The interactions of esomeprazole with MAO-A and MAO-B are reversible and most likely competitive with Ki values for the inhibition of the respective enzymes of 8.99 µM and 31.7 µM. Considering the available pharmacokinetic data and typical therapeutic doses of esomeprazole, these inhibitory potencies are unlikely to be of pharmacological relevance in humans. The MAO inhibitory effects of esomeprazole should however be taken into consideration when using this drug in animal experiments where higher doses are often administered.
Keywords: monoamine oxidase; esomeprazole; inhibition; competitive; reversible